A new electrolytic pencil for the local cleaning of silver tarnish. (3rd May 2016) - Degrigny, Christian; Jeanneret, Romain; Witschard, Denise; Baudin, Carole; Bussy, Gaëtan; Carrel, Hélène
Abstract : The prototyping of a newly designed electrolytic pencil for the local cleaning of silver tarnish on artifacts comprising inseparable organic components is described. The pencil helps determine the type and amount of tarnish, define the cleaning parameters (treatment potential and duration), and provides a safe and efficient way to locally and electrolytically reduce silver tarnish. The electrolyte is conveyed to and from the surface of metal objects via a micro-porous foam and is continuously renewed by two pumps. This user-friendly and ergonomic pencil is distributed as an open source kit for self-assembly with parts fabricated using innovative and low-cost technologies. The operating modes for the pencil are described. To evaluate this new tool, the pencil was used to clean a selection of tarnished silver components from composite masterpieces in the Treasury of Saint-Maurice Abbey.